Mempromosikan Energi Terbarukan: Diplomasi Lingkungan Indonesia dalam Menanggulangi Perubahan Iklim [Promoting Renewable Energy: Indonesia's Environmental Diplomacy in Tackling Climate Change] - Nasution, Elyzabeth Bonethe; Rolliansyah, Dylan Andre; Roring, Hanna Angel; Rino, Meyer Rafael; Lanjari, Rara Nindya Wijayantika (Universitas Pelita Harapan, 2023)
Providing sustainable energy has become a global priority in the face of increasingly alarming climate change. Renewable energy is a key solution to minimize environmental impact, reduce greenhouse gas emissions, and decrease reliance on fossil fuels that accelerate climate change. Indonesia, with its significant potential for renewable energy, has adopted strategies and policies supporting the development of renewable energy, emphasizing the role of environmental diplomacy in achieving these goals. Indonesia's position in regional and global geopolitics also influences the applied renewable energy policies. This study employs qualitative research methods and secondary data collection to gather information from literature sources, government reports, scientific journals, and news articles. This method allows researchers to analyze historical data, policies, and practices related to renewable energy in Indonesia, providing a comprehensive overview of Indonesia's diplomatic strategies for adopting and promoting renewable energy. The research will be analyzed from a neoliberal institutionalism perspective, emphasizing the importance of international institutions in achieving goals. Indonesia seeks international partnerships to develop and invest in renewable energy projects. This reflects a neoliberal institutionalist approach to energy sector development, with an emphasis on cooperation among states, technology transfer, and access to global financial resources. Through the neoliberal institutionalism framework, Indonesia's environmental diplomacy strategy in renewable energy development reflects the government's efforts to achieve balanced economic, environmental, and foreign policy goals. This research aims to delve into Indonesia's environmental diplomacy contributions to successfully implementing and promoting its renewable energy policies, anchored on neoliberal principles in addressing climate change.